Enhancement of the reductive activation of chloroplast fructose‐1,6‐bisphosphatase by modulators and protein perturbants - Ballicora, M.A. (1994)
To characterize the mechanism of chloroplast fructose‐1,6‐bisphosphatase activation, we have examined kinetic and structural changes elicited by protein perturbants and reductants. At variance with its well‐known capacity for enzyme inactivation, 150 mM sodium trichloroacetate yielded an activatable chloroplast fructose‐1,6‐bisphosphatase in the presence of 1.0 mM fructose 1,6‐bisphosphate and 0.1 mM Ca2+. Other sugar bisphosphates did not replace fructose 1,6‐bisphosphate whereas Mg2+ and Mn2+ were functional in place of Ca2+. Variations of the emission fluorescence of intrinsic fluorophores and a noncovalently bound extrinsic probe [2‐(P‐toluidinyl)naphthalene‐6‐sulfonate] indicated the presence of conformations different from the native form. A similar conclusion was drawn from the analysis of absorption spectra by means of fourth‐derivative spectrophotometry. The effect of these conformational changes on the reductive process was studied by subsequently incubating the enzyme with dithiothreitol. The reaction of chloroplast fructose‐1,6‐bisphosphatase with dithiothreitol was accelerated 13‐fold by the chaotropic anion: second‐order rate constants were 48.1 M−1· min−1 and 3.7 M−1· min−1 in the presence and in the absence of trichloroacetate, respectively. Thus, the enhancement of the reductive activation by compounds devoid of redox activity illustrated that the modification of intramolecular noncovalent interactions of chloroplast fructose‐1,6‐bisphosphatase plays an essential role in the conversion of enzyme disulfide bonds to sulfhydryl groups. In consequence, a conformational change would operate concertedly with the reduction of disulfide bridges in the light‐dependent activation mediated by the ferredoxin–thioredoxin system. Copyright © 1994, Wiley Blackwell. All rights reserved